KUALITAS KIMIA, FISIK DAN SENSORI KEFIR SUSU KAMBING YANG DISIMPAN PADA SUHU DAN LAMA PENYIMPANAN BERBEDA - triana setyawardani; Juni Sumarmono; Agustinus Hantoro Djoko Rahardjo; Mardiati Sulistyowati; Kusuma Widayaka (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
The objective of this research was to investigate the chemical, physical and sensory properties of goat milk kefir during storage under different temperatures and storage time. Experimental method, applied completely randomized factorial design. The first factor was temperature (-1 to -5oC; 5 to 10oC and 6 to 10oC) and the second factor was storage time (10; 20 and 30 days) followed by Duncan test. Result showed that temperature, storage time and interaction highly significantly affected (P<0.01) the level of ethanol and FFA, but not affected (P>0.05) on protein content, fat and ash but CO2 level, texture and flavor of kefir were affected by storage time. Kefir viscosity was only affected by storage temperature (P<0.05). Research concluded that storage temperature affected chemical properties such as ethanol, FFA and kefir viscosity,while kefir sensory properties was predominantly affected by storage